Editorial 9.2 - Lefoe, Geraldine (Journal of University Teaching and Learning Practice, 2012)
With this second issue of Volume 9 of the Journal of Teaching and Learning Practice we bring a warm welcome to new members of the Editorial board. The board will be strengthened by their contributions. The Senior Editors are Associate Professor Geraldine Lefoe, University of Wollongong, Australia and Dr Meg O’Reilly, Southern Cross University, Australia. Our editorial board includes members of the host institution (University of Wollongong), Dr Lynne Keevers, Ms Lucia Tome, Associate Professor Greg Hampton, Dr. Michael Jones, Associate Professor Anne Porter, and Dr. Dominique Parrish. Our external board members include Ms Jude Carroll, Associate Professor Andrew Furco, Professor Terence Lovat, and Ms Carolyn Webb. We have particularly appreciated the support of the University of Wollongong’s Deputy Vice Chancellor (Academic) Professor Rob Castle who has recently retired. His patronage and support of our journal has seen it move from a small internal journal to a much larger international journal. He has been a great champion for teaching and learning in the local and national arena and his contributions to the institution and to the sector have been greatly valued. We wish him well in his retirement and know that he will continue his contributions to the sector in the years to come.